Distinct roles of two myosins in C. elegans spermatid differentiation. - Junyan Hu; Shiya Cheng; Haibin Wang; Xin Li; Sun Liu; Mengmeng Wu; Yubing Liu; Xiaochen Wang (PLoS Biology, 2019)
During spermatogenesis, interconnected haploid spermatids segregate undesired cellular contents into residual bodies (RBs) before detaching from RBs. It is unclear how this differentiation process is controlled to produce individual spermatids or motile spermatozoa. Here, we developed a live imaging system to visualize and investigate this process in C. elegans. We found that non-muscle myosin 2 (NMY-2)/myosin II drives incomplete cytokinesis to generate connected haploid spermatids, which are then polarized to segregate undesired cellular contents into RBs under the control of myosin II and myosin VI. NMY-2/myosin II extends from the pseudo-cleavage furrow formed between two haploid spermatids to the spermatid poles, thus promoting RB expansion. In the meantime, defective spermatogenesis 15 (SPE-15)/myosin VI migrates from spermatids towards the expanding RB to promote spermatid budding. Loss of myosin II or myosin VI causes distinct cytoplasm segregation defects, while loss of both myosins completely blocks RB formation. We found that the final separation of spermatids from RBs is achieved through myosin VI-mediated cytokinesis, while myosin II is dispensable at this step. SPE-15/myosin VI and F-actin form a detergent-resistant actomyosin VI ring that undergoes continuous contraction to promote membrane constriction between spermatid and RB. We further identified that RGS-GAIP-interacting protein C terminus (GIPC)-1 and GIPC-2 cooperate with myosin VI to regulate contractile ring formation and spermatid release. Our study reveals distinct roles of myosin II and myosin VI in spermatid differentiation and uncovers a novel myosin VI-mediated cytokinesis process that controls spermatid release.